The Use of Visual Media in Early Literacy Learning in Kindergarten - Dalia Rimavičienė; Nicholas Zaranis; Evanthia Synodi (Zabags International Journal of Education, 2025)
Early childhood education plays a crucial role in laying the foundation for literacy, which underpins academic success in later stages. Early literacy encompasses not only reading and writing skills but also the ability to comprehend meaning, recognize symbols, and communicate effectively. However, literacy learning practices in kindergarten continue to face challenges, particularly regarding the underutilization of visual media, which is inherently more aligned with the cognitive characteristics of young children who think concretely and iconically. This study aims to describe the forms of visual media usage in early literacy learning, analyze its contribution to enhancing children’s literacy skills, and identify the supporting and inhibiting factors in its implementation. Employing a qualitative case study approach, data were collected through observations, interviews, and documentation involving teachers, children, principals, and parents in selected kindergarten institutions. Data analysis was conducted thematically using triangulation techniques to ensure validity. The findings reveal that visual media such as flashcards, picture storybooks, animated videos, and interactive teaching aids enhance learning motivation, strengthen memory retention, and facilitate children’s comprehension of literacy concepts. Furthermore, teacher creativity and parental support emerged as key success factors, while limited resources and pedagogical competencies posed major challenges. This study contributes to strengthening the theoretical framework of visual literacy in early childhood education and provides practical implications for teachers, institutions, and policymakers to systematically integrate visual media into the early childhood curriculum.